Mediasi Sebagai Salah Satu Alternatif Penyelesaian Sengketa Kontrak Showbiz Di Luar Pengadilan - Dion Amando Sihombing, Dion Amando Sihombing (JUSTITIA : Jurnal Ilmu Hukum dan Humaniora, 2021)
In showbiz contract disputes, the disputing parties often take action to resolve the showbiz contract dispute through litigation or courts, there are other ways that the disputing parties can choose, namely through Mediation which is part of Dispute Resolution in Court (Alternative). dispute). The purpose of this study was to determine the legal aspects in the mediation process for the settlement of showbiz business contracts and to find out the obstacles faced in the mediation process for resolving business disputes. This study will discuss from a normative perspective which is then compared with the facts that occur in the field and uses a theoretical approach from several references. From the results of the settlement that mediation is a peace process that takes place and is held between the disputing parties and the settlement by a mediator in order to reach a final agreement that is fair, cost effective, but still effective and fully accepted by the parties. opinions / views of experts, the techniques and varied varied. the existence of mediation in the legal and political system must be seen as an effort to realize the broadest sense of justice. Justice can be achieved by deciding through court or arbitration, but it can also be achieved through deliberation and consensus methods such as negotiation and mediation.